Cost of illness of advanced ovarian carcinoma in Italy: results of an empirical, single-centre study - Lazzaro, Carlo; Plotti, Francesco; Capriglione, Stella; Ferrario, Matteo; Angioli, Roberto (Farmeconomia. Health Economics and Therapeutic Pathways, 2015)
AIM: To perform an empirical, single-centre, retrospective and secondary cost of illness (COI) study of advanced ovarian carcinoma (AOC) in Italy. METHODS: Demographic, clinical, health care and non-health care resource consumption data concerning a convenience sample of subsequent patients in 1st line of treatment (100 patients), 2nd line of treatment A (surgery + chemotherapy; 30 patients) and 2nd line of treatment B (chemotherapy only; 20 patients) were obtained from a database created in 2011 by the Obstetrics and Ginecology Unit at Campus Biomedico teaching hospital, Rome. Patients were followed-up for 2 years. Resources were valued according to the above mentioned database and literature, following the societal viewpoint. Costs are expressed in Euro (€) 2014 and reported as mean and standard deviation (SD). RESULTS: One-year COI for 1st line of treatment reaches € 44,999.7 (SD: €28,757.3), € 55,410.8 (SD: € 32,454.6) and €46,895.6 (SD: € 28,407.4) for 2nd line of treatment A and B, respectively. Regardless the line of treatment, COI is mainly driven by cost borne by patient and her family. Due to the high costs of relapse the mean COI per patient after 2 years from the diagnosis of AOC equals € 81,869.4 (SD: € 30,660.9), or 182% of the COI for the 1st line of treatment. CONCLUSIONS: Despite some limitations, our results show that increasing progression-free survival could well reduce the COI for AOC in Italy.